Comparative analysis of the intestinal flora of Siniperca chuatsi at different growth stages under three feeding practices - Yunyun Yan; Fubao Wang; Xiao Chen; Junjian Dong; Fengying Gao; Hetong Zhang; Xing Ye; Chengbin Wu; Chengfei Sun (Aquaculture Reports)
The intestinal flora plays a key role in digestion and nutrient absorption, and its composition in fish can vary depending on feeding practices and growth stages. Siniperca chuatsi feeds on live bait throughout its life, and preliminary developments have been made for compound feed as an alternative to live bait in aquaculture. We investigated changes in the intestinal flora of S. chuatsi under three different feeding practices (live bait, compound feed, and mixed diet) at different growth stages by 16S rRNA sequencing. A total of 4,220,390 valid sequences were obtained, clustered into 9103 ASVs. The intestinal flora of S. chuatsi was dominated by Pseudomonadota, Firmicutes, and Bacteroidota. With growth, the α-diversity of the intestinal flora in the live bait group and mixed diet group significantly decreased (p < 0.05), while the α-diversity in the compound feed group did not change significantly (p > 0.05). There were no significant differences in α-diversity among the feeding practices at either one month or two months of age (p > 0.05). At three months of age, the α-diversity was significantly higher in the compound feed group compared to the mixed diet group or live bait group (p < 0.05). Functional prediction revealed that the carbohydrate metabolism pathway was most enriched in the compound feed group, while the amino acid metabolism pathway was most enriched in the live bait group. In the mixed diet group, both the amino acid metabolism and carbohydrate metabolism pathways were similarly enriched. A relatively high number of marker genera were observed in the compound feed group, of which Stenotrophomonas and Cetobacterium are potentially valuable in the application of feed additives for S. chuatsi. This study provides insights into the adaptation mechanisms of intestinal flora to compound feed, supporting diet domestication and the optimization of compound feed formulation for S. chuatsi.